Influences of COVID-19 vaccination policy on students' vaccine acceptance - Thuli G. Mthembu; Samantha Harrison; Kauthar Botha; Jessica Britz; Brittney Katts; Michaela Millar; Zia Sulliman; Vutlhari Zitha (AOSIS, 2023)
Background: Higher education institutions (HEIs) developed and implemented a mandatory COVID-19 vaccination policy to facilitate vaccine acceptance and vaccination among universities' staff and students. However, little is known about influences of the mandatory vaccination policy on health science students at a university and they tend to result in vaccine hesitancy. Aim: To explore the influences of the mandatory COVID-19 vaccine policy on health sciences students' vaccine acceptance at HEIs in South Africa. Setting: The study was conducted in one of the universities in the Western Cape Province, South Africa. Methods: An interpretive qualitative exploratory-descriptive research was conducted with 10 participants who were selected using the purposive sampling method to participate in semi-structured interviews. Data were audio-recorded, transcribed verbatim and thematically analysed. Results: Two themes and 12 sub-themes were identified during the data analysis, namely individual and group influencing factors, as well as contextual influencing factors. Conclusion: This study revealed that the COVID-19 vaccination mandatory policy influenced the students' quality of life, academic performance and well-being. The findings from this study indicate that there were perceived barriers related to personal and contextual influencing factors than benefits of COVID-19 vaccination. Contribution: The understanding of and insight into the influences of the mandatory vaccination policy provided a basis for further strategies that may be developed to address COVID-19 vaccine infodemic, vaccine hesitancy and its risk effects. This can be done through collaboration with different stakeholders to educate health science students about the perceived benefits of COVID-19 vaccination.